Seeds inoculation with diazotrophic bacteria and nitrogen application in side-dressing and leaf in maize - Kappes, Claudinei; Arf, Orivaldo; Arf, Marcelo Valentini; Ferreira, João Paulo; Dal Bem, Edjair Augusto; Portugal, José Roberto; Vilela, Rafael Gonçalves (Semina: Ciências Agrárias, 2013)
Considering the importance of nitrogen management and its biological fixation with diazotrophic bacteria, this study was carried out aiming to evaluate the agronomic performance of maize, in response to seed inoculation with Azospirillum brasilense and nitrogen application in side-dressing and leaf. The experiment was conducted in Selvíria, Mato Grosso of Sul State, Brazil, during the growing season 2010/2011, on a clayey Rhodic Haplustox (20º 20' S and 51º 24' W, with altitude of 340 m). Sixteen treatments were established with four replications, in randomized blocks with the combination of the factors A. brasilense (with and without inoculante), nitrogen rate (0 and 90 kg ha-1, in V5 growth stage) and urea leaf application (0, 4, 8 and 12%: application in V5 and V8 growth stage). The maize hybrid used was the DKB 390 YGÂ®, sowed in the row spacing of 0.9 m. Parameters measured were productive and morphological components of culture and crop yield. Increase in maize yield by seed inoculation with A. brasilense was observed. The application of 90 kg ha-1 of nitrogen in side-dressing provided higher chlorophyll leaf index, stalk diameter and prolificacy, however, the yield not was increased. The application of urea leaf did not agronomic efficiency and, therefore, should not be used as the unique form of supply and alternative to nitrogen addition to crop.